PERANCANGAN DESAIN USER INTERFACE DAN USER EXPERIENCE APLIKASI PENJUALAN BERBASIS MOBILE MENGGUNAKAN METODE USER CENTERED DESIGN (STUDI KASUS: CV MEGA STEEL) - Pricillia Temmy Keliwulan; Imam Maruf Nugroho; Yudhi Raymond R (INFOKOM (Informatika & Komputer), 2023)
CV Mega Steel is a business engaged in roof construction materials such as spandex, gypsum, ceiling, bondeck, wiremesh, and others. The problems found in CV Mega Steel in sales and transactions still use manual processes such as coming directly to the place. In addition, marketing at CV Mega Steel is less widespread, because the media used is only in the form of brochures and is marketed in the region around Purwakarta. This study aims to create an application interface display for CV Mega Steel with the help of an interface prototype. This application is expected to help and support business activities by expanding marketing reach and making it easier for customers and sellers through good design in terms of user interface and user experience. The method used in this study is the user centered design method which has 4 stages, namely specifying the context of use, specifying user and organizational requirements, producing design solutions and evaluating designs. Tests were carried out on 30 respondents using the user experience questionnaire method with calculations using a Likert scale. With the results of the value of Attractiveness 1.639, Clarity 1.733, Efficiency 1.775, Accuracy 1.450, Stimulation 1.142, and Novelty 0.867 shows that all aspects get a positive impression, this shows that the design of UI / UX mobile-based sales applications can be used by customers as a means of transaction in CV Mega Steel.